SELUBUNG HISTORIOGRAFI SYEKH MAULANA MAGHRIBI WONOBODRO (Jurnal Penelitian, 2015)
This study aimed to reveal the understanding and perceptions of the public upon history of Sheikh Maulana Maghribi’s (SMM) tomb and character. This qualitative approach used historical research. The results showed that the SMM’s history of the tomb and his figures are still remembered and understood among Wonobodro community through two ways, namely: through word of mouth from family members or other people hereditary and through oral explanation from the manager of the tomb complex, especially Interpreter Lock to pilgrims. In addition, it was also revealed that there are two different informants understanding about the real identity of Sheikh Maulana Maghribi. It is caused by lack of depth information obtained by Wonobodro community. The conclusion that there is character and story elements that reflect the similarities of culture, values and experience of informants and community.
Keywords: Makam; syekh Maulana Maghribi; sejarah lisan